2021
DOI: 10.7759/cureus.16250
|View full text |Cite
|
Sign up to set email alerts
|

A Modification to a Murine Model for Intracranial Aneurysm Formation and Rupture

Abstract: Between 3.6% and 6.0% of the population has an intracranial aneurysm. The mechanisms underlying intracranial aneurysm formation and rupture are not fully known. Several rodent models have been developed to better understand intracranial aneurysm pathophysiology. Hypertension, hemodynamic changes, and vessel injury are all necessary for aneurysm induction; however, multiple invasive procedures may disrupt an animal's physiology. Therefore, we hypothesized that our method for inducing hypertension could be modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Hemodynamic stress is induced by using a combination of surgical strategies, including common carotid artery ligation, bilateral renal artery ligation, unilateral nephrectomy, and administration of pharmacological agents, including deoxycorticosterone or angiotensin II with increased NaCl in drinking water or food. 5 , 6 , 19 , 25 , 26 , 41 , 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemodynamic stress is induced by using a combination of surgical strategies, including common carotid artery ligation, bilateral renal artery ligation, unilateral nephrectomy, and administration of pharmacological agents, including deoxycorticosterone or angiotensin II with increased NaCl in drinking water or food. 5 , 6 , 19 , 25 , 26 , 41 , 46 …”
Section: Discussionmentioning
confidence: 99%
“… 26 Recently, Patel et al further modified the model generated by Hosaka et al, and showed that right renal artery ligation did not affect the incidence of IA formation and rupture. 41 Starke et al developed the IA mouse model by using nephrectomy, and 1 week later, a deoxycorticosterone pellet was implanted, 1% NaCl in water was started with 0.12% β‐aminopropionitrile, and elastase (35 mU) was injected into the right basal cistern. 5 IAs were formed in 81.8% of the mice, and the incidence of ruptured IAs was observed in 68.2% of mice.…”
Section: Methodsmentioning
confidence: 99%
“…The aneurysm model can be established by ligating the common carotid artery and inducing hypertension by injecting cortisol and diet as well, but it has the problem of uncontrollable aneurysms ( Tang et al, 2020-10 ). It has been reported that intracranial aneurysms can be induced by the degradation of the vascular wall caused by the use of elastase and lysyl oxidase inhibitors, as well as hypertension caused by a high-salt diet, continuous infusion of angiotensin II and ligation of the right renal artery, but the methods are complex and there are many uncontrollable factors ( Patel et al, 2021 ). Compared with these methods, the effect of ligating the lingual artery in dogs is accurate, and the aneurysm model can be established stably and controllably with fewer long-term complications, thereby improving the success rate of model establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Elastase is able to degrade a variety of proteins, prevent cholesterol synthesis in the body, and promote its conversion to cholicacid. In recent years, elastase has been used to induce animal models such as intracranial aneurysm, cervical common aneurysm, abdominal aortic aneurysm in rabbits, emphysema, chronic obstructive pulmonary disease, and osteoporosis ( 23 28 ), which can obviously induce the pathological changes of the target blood vessels and tissues with the advantages of simple, convenient and high success rate. Elastase can be extracted and purified from the animal pancreas, which pertains to the endopeptidase and contains 240 amino acid residues with the isoelectric point of 9.5 ( 29 ) and the best pH value of 8.1–8.8.…”
Section: Discussionmentioning
confidence: 99%